2017
DOI: 10.5194/amt-10-4209-2017
|View full text |Cite
|
Sign up to set email alerts
|

The novel HALO mini-DOAS instrument: inferring trace gas concentrations from airborne UV/visible limb spectroscopy under all skies using the scaling method

Abstract: Abstract. We report on a novel six-channel optical spectrometer (further on called mini-DOAS instrument) for airborne nadir and limb measurements of atmospheric trace gases, liquid and solid water, and spectral radiances in the UV/vis and NIR spectral ranges. The spectrometer was developed for measurements from aboard the German High-Altitude and Long-Range (HALO) research aircraft during dedicated research missions. Here we report on the relevant instrumental details and the novel scaling method used to infer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(53 citation statements)
references
References 85 publications
(116 reference statements)
2
48
0
Order By: Relevance
“…It is further in agreement with R GF inferred from satellite measurements (Chan Miller et al, 2014, 2017DiGangi et al, 2012;Wittrock et al, 2006). For R MF , we infer a range of 0.09 to 1.5 with R MF =0.98 (or respectively smaller results when correcting the C 3 H 4 O * 2 mixing ratios by a factor of 2.0 ± 0.5), which overlaps with the lower end of the range of normalized excess mixing ratios previously reported by Hays et al (2002) for different types of fuels in the laboratory.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…It is further in agreement with R GF inferred from satellite measurements (Chan Miller et al, 2014, 2017DiGangi et al, 2012;Wittrock et al, 2006). For R MF , we infer a range of 0.09 to 1.5 with R MF =0.98 (or respectively smaller results when correcting the C 3 H 4 O * 2 mixing ratios by a factor of 2.0 ± 0.5), which overlaps with the lower end of the range of normalized excess mixing ratios previously reported by Hays et al (2002) for different types of fuels in the laboratory.…”
Section: Discussionsupporting
confidence: 89%
“…Our results are consistent with recent laboratory studies on biomass burning emissions by Zarzana et al (2018) as well as different field measurements and satellite observations by Chan Miller et al (2014, 2017; DiGangi et al (2012); Wittrock et al (2006) and Zarzana et al (2017). From laboratory measurements, Zarzana et al (2018) reported an average R GF of 0.068 for fresh emissions and different kinds of fuels.…”
Section: R Gfsupporting
confidence: 92%
“…They are the mini-DOAS instrument for remote sensing measurements of O 3 , NO 2 , and BrO (Hüneke et al, 2017), FAIRO (Fast Airborne Ozone monitor) for the measurements of in situ O 3 (Zahn et al, 2012), GhOST (Gas chromatograph for the Observational Studies using Tracers) for the in situ measurements of the organic brominated source gases (Sala et al, 2014) and SF 6 mean air mass lag-times (Bönisch et al, 2009), and UMAQS (University of Mainz Airborne QCL (quantum cascade laser) Spectrometer) for in situ measurements of air mass transport tracers N 2 O and CO (Müller et al, 2015;Kunkel et al, 2019).…”
Section: Instruments and Methodsmentioning
confidence: 99%
“…The possible influence of horizontal advection and blowing snow is limited in the data set by applying an upper limit for the wind speed of 6 m s −1 . Note that previous studies pointed to 8 m s −1 as the wind threshold for blowing snow (e.g., Jones et al, 2009) and others indicated that the steady-state approximation is valid for wind speeds lower than the 6 m s −1 threshold considered here (e.g., Liao et al, 2012). Based on Eq.…”
Section: Bro X In Antarcticamentioning
confidence: 58%